Is the very low carbohydrate diet safe for individuals with chronic kidney disease? - Brooke S. Colledge; Emma C. Schofield; Benjamin J. Clarke; Gordana Popovic; Mohandas Vattekad; Penelope E. Figtree (Journal of Metabolic Health)
Background: The very low carbohydrate diet (VLCHD) is gaining popularity as a therapy for metabolic syndrome. However, its effect on renal function in patients with comorbid moderate to severe chronic kidney disease (CKD) is currently unclear.